(untitled) - Kovalick, Al (Amsterdam, 2006)
Audio/Video (AV) systems and Information Technology (IT) are colliding. Broadcasters and other AV professionals are impacted by the transition to IT components and techniques. This is the first book to focus on the intersection of AV and IT concepts. It includes technology reviews and the tools to understand and evaluate key aspects of hybrid AV systems. Twelve chapters encompass a broad range of information including: IT integration, AV networking, storage systems, file and metadata formats, software platforms, reliability, element management, security, workflow improvement, AV technology, transition issues, and real-world case studies. Each chapter weaves together IT and AV techniques providing the reader with actionable information on the issues, processes and principles of seamless AV/IT systems integration.
Keywords: Digital video,Multimedia systems,Digital media,Video kỹ thuật số.,Hệ thống đa phương tiện,Truyền thông số